Statistical Cross Layer Adaptation in Fast Fading Mobile Satellite Channels - Alberto Rico-Alvariño; J. Arnau; C. Mosquera (Globecom 2013 - Symposium on Selected Areas in Communications (GC13 SAC), 2013)
Link adaptation in mobile satellite channels is difficult because of the large propagation delays, the frequent signal blockage and the variation of the channel statistics. In this paper, we propose a cross-layer link adaptation strategy that exploits statistical, long-term CSI to increase the throughput when some retransmissions are available; this increase is obtained while meeting a target outage probability constraint. Our strategy takes as inputs the estimated packet error rates of the available modulation and coding schemes (MCS) and their rates; as an output, it returns the optimum sequence of MCS to be used. Results will also show that simple information acquisition strategies can still provide very good results.
Keywords: dynacs; fast fading channels; link adaptation; mobile satellite; satcom